The Modern Character of Mental Health Stigma: A 30-Year Examination of Popular Film. Issue 4 (4th July 2021) - Riles, Julius Matthew; Miller, Brandon; Funk, Michelle; Morrow, Ethan
ABSTRACT: Popular film contains an abundance of information pertaining to identity and stigma attributions popularly linked with those experiencing mental health concerns. However, this domain remains under-examined with regard to health identity representations, notably as they intersect with other social identities. Thirty years of the most popular films emphasizing mental health were content analyzed for the purpose of obtaining a contemporary assessment of the stigmatizing potential of representation patterns, notably, extending beyond popularly established associations of mental illness with danger. Distortions were observed disproportionately connecting those experiencing mental illness with stigmatizing attributes in myriad ways, including risky health behaviors (e.g., drinking alcohol, smoking cigarettes, eating issues), various forms of aggression (e.g., physical, verbal, sexual), and reactions to adversity (e.g., crying, attempting self-harm, and having struggles diminished by others). Additionally, evidence suggests a relative dearth of displaying the experiences of non-culturally dominant social identities and their intersections with mental health identity. Prior research has indicated that that mediated portrayals of those experiencing mental illness can influence self-perceptions and social inclinations pertaining to this health identity. Findings are discussed in terms of these potential outcomes.